Pengaruh Motivasi Kerja dan Pelatihan Kerja terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Barito Kuala - Hanifah, Hanifah; Sari, Erini Junita; Yani, Ni Kadek Adwy (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the influence of work motivation and job training on employee performance at the Population and Civil Registration Office of Barito Kuala Regency. Using a quantitative approach with questionnaires distributed to 45 employees through saturated sampling, data were analyzed with multiple linear regression using SPSS 26. Results showed that work motivation (t = 3.537, p = 0.001) and job training (t = 2.950, p = 0.005) both had positive and significant effects on performance. Simultaneously, both variables significantly influenced performance (F = 74.356, p = 0.000), with work motivation and job training explaining 78% of the variance in employee performance.